Linkages between mineralogy, fluid chemistry, and microbial communities within hydrothermal chimneys from the Endeavour Segment, Juan de Fuca Ridge. (5th February 2016) - Lin, T. J.; Ver Eecke, H. C.; Breves, E. A.; Dyar, M. D.; Jamieson, J. W.; Hannington, M. D.; Dahle, H.; Bishop, J. L.; Lane, M. D.; Butterfield, D. A.; Kelley, D. S.; Lilley, M. D.; et al.
Abstract: Rock and fluid samples were collected from three hydrothermal chimneys at the Endeavour Segment, Juan de Fuca Ridge to evaluate linkages among mineralogy, fluid chemistry, and microbial community composition within the chimneys. Mössbauer, midinfrared thermal emission, and visible‐near infrared spectroscopies were utilized for the first time to characterize vent mineralogy, in addition to thin‐section petrography, X‐ray diffraction, and elemental analyses. A 282°C venting chimney from the Bastille edifice was composed primarily of sulfide minerals such as chalcopyrite, marcasite, and sphalerite. In contrast, samples from a 300°C venting chimney from the Dante edifice and a 321°C venting chimney from the Hot Harold edifice contained a high abundance of the sulfate mineral anhydrite. Geochemical modeling of mixed vent fluids suggested the oxic‐anoxic transition zone was above 100°C at all three vents, and that the thermodynamic energy available for autotrophic microbial redox reactions favored aerobic sulfide and methane oxidation. As predicted, microbes within the Dante and Hot Harold chimneys were most closely related to mesophilic and thermophilic aerobes of the Betaproteobacteria and Gammaproteobacteria and sulfide‐oxidizing autotrophic Epsilonproteobacteria . However, most of the microbes within the Bastille chimney were most closely related to mesophilic and thermophilic anaerobes of the Deltaproteobacteria, especially sulfate reducers, and anaerobic hyperthermophilic archaea. The predominance of anaerobes in the Bastille chimney indicated that other environmental factors promote anoxic conditions. Possibilities include the maturity or fluid flow characteristics of the chimney, abiotic Fe 2+ and S 2− oxidation in the vent fluids, or O2 depletion by aerobic respiration on the chimney outer wall. Key Points: Emissivity and reflectance spectroscopies used for first time on vent samples Spectroscopies corroborated petrography, XRD, and elemental analyses Conditions within metal‐sulfide edifices may promote anaerobic metabolisms